Idiopathic myelofibrosis with disseminated hepatosplenic, mesenteric, renal and pulmonary extramedullary haematopoeisis, portal hypertension and tuberculosis: initial presentation and 2 years follow-up. (23rd December 2016) - Panda, Ananya; Chandrashekhara, Sheragaru Hanumanthappa; Nambirajan, Aruna; Mishra, Pravas
Abstract : A 35-year-old man with a 12-year history of idiopathic myelofibrosis (IMF) presented in 2014 with fatigue and abdominal distension. CT scan revealed massive hepatosplenomegaly with focal splenic lesions, soft tissue around renal pelvis, mesenteric masses compressing bowel loops and perilymphatic nodules in lungs. There was portal hypertension, ascites, pleural effusion, bilateral psoas abscesses and necrotic retroperitoneal lymphadenopathy. MRI additionally revealed hypointense periportal infiltrative lesions in liver, not seen on CT scan. None of these lesions showed diffusion restriction. Biopsy from mesenteric masses revealed extramedullary haematopoeisis. Aspiration from psoas abscess confirmed tuberculosis. Follow-up after 6 weeks of ruxolitinib (JAK2 tyrosine kinase inhibitor) and 9 months of antitubercular therapy revealed resolution of psoas abscesses and lymph nodes. Mild reduction was noted in mesenteric masses and ascites while perirenal soft tissue had increased. Follow-up imaging after another 1 year of ruloxitinib showed new-onset bilateral paravertebral and presacral foci of extramedullary haematopoeisis.